A God for Two Women: Construing Religion in Charlotte Brontë’s Jane Eyre and Jean Rhys’ Wide Sargasso Sea - Cabello Bravo, Andy (Journal of Artistic Creation and Literary Research, 2025)
The advent of post-colonialism as an approach to literary texts opened a new route for critics to assess many of the Victorian classics. The light in which the canon saw Jane Eyre changed as regards Brontë’s treatment of the Creole character, Bertha Mason, later revitalised as Antoinette Cosway in Wide Sargasso Sea . Aside from racial and gender issues, which this paper must integrate, religion plays a key role in the two novels. The guidance the religion of the heart can afford the heroines heavily relies upon their experience and interpretation of the hostile world by which they must abide. Their success or failure, their apprehension or values and demeanours, will be influenced by their capacity to turn God into an ally. A revision of the strategies they apply is implemented hand in hand with their biography to appraise both singularities and points of confluence. The Christian discourse, the figure of Mr Rochester, and the overlaps of Antoinette and Jane’s story thus constitute a rich source of material to draw upon for the analysis of female religious experience.